The Asian Development Bank and the production of poverty: Neoliberalism, technocratic modernization and land dispossession in the Greater Mekong Subregion. Issue 1 (26th February 2015) - Sims, Kearrin
<x xml:space="preserve">Abstract</x> In 1992 the Asian Development Bank coordinated a meeting between government representatives from China, Cambodia, Laos, Myanmar, Thailand and Vietnam to discuss regional economic integration. From that meeting the Greater Mekong Subregion was formed to promote peace and prosperity within the Mekong countries. Yet, despite more than more than USD 14 billion being spent on facilitating trade, development and infrastructural ties between these nations, poverty remains widespread. This article provides a critical analysis of the Asian Development Bank and its approach to development and poverty alleviation within the Greater Mekong Subregion. It suggests that the institution's technocratic neoliberal development ideology provides a discursive legitimation to processes of displacement and dispossession that has seen the production of new forms of poverty. To make this argument, the article draws on an ethnographic study of the local‐scale implications of forced resettlement at the Luang Prabang Airport. It conducts an analysis of how the Asian Development Bank defines and measures poverty, and critiques the institution's resettlement guidelines for the airport project.